Lifestyle Behaviour and Obstructive Sleep Apnea (OSA): An Association Study Among Young Adults - Remya Krishnan Jyothi; Mathangi Damal Chandrasekhar; Vinoth Chellaiyan Devanbu (Medsci Publications, 2022)
Introduction: Lifestyle changes like low physical activity, smoking and consumption of alcohol have been reported to have an impact on Obstructive Sleep Apnea. Smoking was found to be associated with nocturnal hypoxemia and disturbed sleep. Apneic episodes are increased after alcohol consumption. Objectives: To determine the risk of developing Obstructive Sleep Apnea among young adults. Material and Methods: Participants were asked to fill in an online generated questionnaire on lifestyle habits in addition to the modified Berlin questionnaire and Epworth questionnaire. A total of 209 study participants were included in the study. A Chi-square test was applied. Results: Among 209 participants, 47(22.5%) were females and 162 (77.5%) were males. Snoring was reported in 90 (43.1%) of study participants. Around thirty-three, percent of participants were at higher risk of developing Obstructive Sleep Apnea and Obstructive Sleep Apnea was predicted in 21.5%. No association was found between the lifestyle behavioural factors and Obstructive Sleep Apnea. Conclusion: Though a significant association was not found between selected lifestyle factors and Obstructive Sleep Apnea risk, the role of lifestyle factors could not be undermined. A healthy lifestyle helps in preventing the occurrence of Obstructive Sleep Apnea.